Combined Metronomic Chemo-Immunotherapy for Metastatic Esophageal Carcinoma in Second-Line and Beyond - Kallolli, Mahesh; Madabhavi, Irappa V; Chavan, Chidanand; Revannasiddaiah, Swaroop; Gupta, Ishu; S. Sarkar, Malay (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Approximately 570,000 new cases of esophageal cancer are diagnosed worldwide annually, resulting in approximately 510,000 deaths per year. Currently, there are no effective second-line treatments for patients who progress on cisplatin and 5-fluorouracil. Esophageal squamous cell carcinomas and adenocarcinomas have proven to be inherently resistant to systemic treatments due to histological, molecular, and etiological heterogeneity, resulting in limited responses after first-line therapy. Materials and Methods: We present three case reports of patients (a 57-year-old male, a 53-year-old male, and a 47-year-old female) who presented with dysphagia for solid foods, weight loss, and dyspepsia for 1 month, 3 months, and 1.5 months, respectively. Upper gastroesophageal endoscopy revealed ulcerated, friable lesions with minimal luminal compromise. Biopsies confirmed poorly differentiated adenocarcinoma (PDAC) in all three cases. Positron emission tomography-computed tomography (PET-CT) showed FDG-avid lesions in the gastroesophageal junction, gastric cardia, multiple retroperitoneal lymph nodes, and bilateral liver lesions. All three patients had stage IV disease with PDAC (two patients) and squamous cell carcinoma (one patient). The first patient received a DOX regimen containing docetaxel, oxaliplatin, and capecitabine at 2-week intervals. After four cycles, he demonstrated stable disease in the gastroesophageal junction and liver, with a slight increase in retroperitoneal lymph node size. The second and third patients received a paclitaxel-carboplatin protocol. After six cycles, both patients achieved a partial response and were subsequently managed with six cycles of CAPOX as second-line chemotherapy. Both patients exhibited progressive disease after five and six months of second-line chemotherapy, respectively. Results: In light of radiological progression, the first patient was initiated on intravenous nivolumab (240 mg every two weeks) along with low-dose capecitabine (500 mg twice a day). After four cycles of treatment, a PET-CT scan showed complete metabolic response in the gastroesophageal junction, liver, and retroperitoneal lesions. The patient continues to receive nivolumab and low-dose capecitabine, with a treatment plan of two years. Conclusion: This case series suggests that nivolumab combined with metronomic chemotherapy using low-dose capecitabine is well-tolerated and exhibits antitumor activity in extensively pre-treated patients with metastatic esophageal poorly differentiated adenocarcinoma. Further studies investigating nivolumab, metronomic chemotherapy, and immuno-immuno combination therapy for these diseases are ongoing.